A batch processed titanium–vanadium oxide nanocomposite based solid-state electrochemical sensor for zeptomolar nucleic acid detection. Issue 44 (3rd November 2022) - Agarkar, Tanvi; Tripathy, Sayantan; Chawla, Vipin; Sengupta, Mrittika; Ghosh, Souradyuti; Kumar, Ashvani
Abstract : A bi-electrode sensor with a transition metal oxide-based active layer for electrochemical DNA/RNA amplification detection is developed. The device offers sensitivity towards 10 2 and 10 1 copies of SARS-CoV-2 plasmid and RNA, respectively. Abstract : Approaching a nucleic acid amplification test (NAAT) based diagnosis of a pathogen from an electrochemistry pathway is a relatively economical, decentralized, and yet highly sensitive route. This work aimed to construct an electrochemical biosensor with a 2-electrode geometry using a transition metal oxide (TMO) based sensing layer. A series of batch-processed TiO2 –V2 O5 (TVO) nanocomposite-based electrodes were fabricated to probe their electrochemical performance and attain a highly sensitive dual-electrode electrochemical sensor (DEES) compared to pristine V2 O5 . The XRD analysis of the electrodes confirmed the formation of a nanocomposite, while the XPS analysis correlated the formation of oxygen vacancies with improved electrical conduction measured via EIS and I – V characterization. Furthermore, the work demonstrated the application of the optimized electrode in electrochemical detection of end-point loop-mediated isothermal amplification (LAMP) readout for 10 1 –10 4 copies (0.1 zeptomoles to 0.1 attomoles) of SARS-CoV-2 RNA dependent RNA polymerase (RdRp) plasmid DNA and in vitro transcribed RNA in an aqueous solution. The device achieved a limit of detection as low as 2.5 and 0.25 copies per μL for plasmid DNA and in vitro transcribed RNA, respectively. The DEES was able to successfully detect in situ LAMP performed on magneto-extracted SARS-CoV-2 plasmid and RNA from (a) an aqueous solution, (b) a sample spiked with excess human genomic DNA, and (c) a serum-spiked sample. The DEES results were then compared with those of real-time fluorescence and commercially available screen-printed electrodes (SPEs).